Delayed severe hemothorax caused by a staple line of a bullectomy performed 11 years earlier - Takashi Yamashita; Katsuyuki Asai (Surgical Case Reports, 2023)
Abstract Background At present, relatively few lung surgeries are performed without endostaplers. Although there are few staple-related adverse events, severe events must be shared to improve safety. Case presentation A 74-year-old male suddenly collapsed and was transferred to the Emergency Rescue department. He had shock vitals and contrast-enhanced CT revealed extensive right hemothorax with contrast leakage. He lost consciousness and tension massive hemothorax was suspected. We performed emergency thoracotomy at two sites and were able to achieve hemostasis and save the patient. Upon examining the patient's medical history after his condition stabilized, it was revealed that he was a lung cancer patient who was taking ramucirumab and cilostazol. In addition, the CT scan taken one month before onset revealed the bleeding site of the fifth intercostal artery were almost contact with the staple line from a prior right spontaneous pneumothorax surgery that was performed 11 years previously, which was seemed to damage the intercostal artery. Conclusion Despite the difficulty in achieving hemostasis due to drug administration history, we successfully treated a case of remote period massive hemothorax attributed to staples, thereby saving the patient. When using drugs that increase the risk of bleeding events, it may be important to consider the position of the staple line while assessing the risk. In the emergent or ICU setting, if the initial incision is not effective, the placement of a new second incision may be valuable.